1995
DOI: 10.1002/pip.4670030202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of Cu(In, Ga)(S, Se)2‐based photovoltaic devices: A laboratory and industrial perspective

Abstract: This contribution is a summary of a workshop convened to discuss the characterization and modeling of thin‐film CuInSe2(CIS)‐based solar cells, 17‐19 October 1993, in Estes Park, Colorado. the participants of the workshop are the authors of this paper. the subject matter was examined along four lines: device modeling, characterization, processing, and manufacturing issues. Fundamental numerical modeling has successfully guided device design efforts, including the design of variable band‐gap absorbers. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In order to calculate the potential distribution and electron and hole concentrations in the solar cell layers, Poisson's equation (1) and the steady state continuity equations for electrons (2) and holes (3) are solved simultaneously: rð r 0 rCðx; yÞÞ ¼ qðpðx; yÞ À nðx; yÞ þ N D ðx; yÞ À N A ðx; yÞÞ (1) rJ n ðx; yÞ ¼ ÀqðGðx; yÞ À Rðx; yÞÞ (2) rJ p ðx; yÞ ¼ þqðGðx; yÞ À Rðx; yÞÞ (3) C is the electrostatic potential, while p and n are the hole and electron densities. N D and N A are the ionized donor and acceptor densities.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to calculate the potential distribution and electron and hole concentrations in the solar cell layers, Poisson's equation (1) and the steady state continuity equations for electrons (2) and holes (3) are solved simultaneously: rð r 0 rCðx; yÞÞ ¼ qðpðx; yÞ À nðx; yÞ þ N D ðx; yÞ À N A ðx; yÞÞ (1) rJ n ðx; yÞ ¼ ÀqðGðx; yÞ À Rðx; yÞÞ (2) rJ p ðx; yÞ ¼ þqðGðx; yÞ À Rðx; yÞÞ (3) C is the electrostatic potential, while p and n are the hole and electron densities. N D and N A are the ionized donor and acceptor densities.…”
Section: Theorymentioning
confidence: 99%
“…In order to develop the technology further, numerical modelling and simulation of devices can be used. It has previously been used as a valuable tool to increase the understanding of device operation, but its importance will most likely increase as optimization is required to push the performance per price ratio in production [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has also been evidence that the blocking behavior can be light-dependent [4] and may specifically depend on the deposition of the CdS or ZnO layers [6]. In this case, the behavior may originate at one of the interfaces between the ZnO, CdS, and CulnSe,.…”
Section: Nt R 0 Duct Io Nimentioning
confidence: 99%
“…Because of these properties, the blocking behavior has been attributed to the Mo/CulnSe, back contact. Measurements of the Mo contact to single crystal CulnSe, showed that the contact behavior depended on the defect state concentration of the CulnSe, [5].However, there has also been evidence that the blocking behavior can be light-dependent [4] and may specifically depend on the deposition of the CdS or ZnO layers [6]. In this case, the behavior may originate at one of the interfaces between the ZnO, CdS, and CulnSe,.…”
mentioning
confidence: 98%
“…Measurements of the Mo contact to single crystal CuInSe, showed that the contact behavior depended on the defect state concentration of the CuInSe, [234]. However, there has also been evidence that the blocking behavior can be light-dependent [221] and may specifically depend on the deposition of the CdS or ZnO layers [235]. In this case, the behavior may originate at one of the interfaces between the ZnO, CdS, and CuInSe,.…”
Section: Introductionmentioning
confidence: 99%